Hazard Analysis and Critical Control Point (CCP) determination in cook-chilled beef curry and beef kurma - Abd Lataf, Dora Liyana; Mahyudin, Nor Ainy; Mohammad Rashedi, Ismail Fitry; Hariri, Rasiyuddin; Abdullah, Ahmad Zaki (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA, 2020)
The first principle of HACCP, the hazard analysis, was conducted to identify the potential hazards associated with food production at all stages, assess the likelihood of occurrence and severity of the hazards and to identify control measures. The determination of critical control point (CCP) is when control can be applied and is essential to prevent, eliminate or reduce the identified food safety hazard to an acceptable level. In this study, the hazard analysis and CCP determination for cook-chilled beef curry and beef kurma in a centralised kitchen were carried out. By using the process steps decision tree in MS1480:2007 standard, two processes were determined as CCPs, which were the boiling process and rapid chilling process.